Professional Development and Differentiated Instruction in an Elementary School Pullout Program: A Gifted Education Case Study. (December 2019) - Brigandi, Carla B.; Gilson, Cindy M.; Miller, Myriah
The purpose of this longitudinal case study was to investigate the relationship between participation in professional development in Renzulli's Enrichment Triad Model and one gifted education teacher's knowledge and practice, with particular attention to differentiated instruction. Findings indicated that professional development increased the participating teacher's knowledge of gifted education, her attitude toward change, and her repertoire of instructional strategies; however, it did not alter her underlying beliefs or subsequent approach to gifted education. Time span and provider support were noted as promoters of effective professional development. Conceptual blocks, teacher characteristics, and lack of time were identified as barriers that inhibited professional development–related change with regard to differentiated instruction for learners who have high academic ability.